Heparin cross‐linked collagen sponge scaffolds improve functional regeneration of rat tracheal epithelium. (19th January 2017) - Nakamura, Ryosuke; Tani, Akiko; Yoshie, Susumu; Ikeda, Masakazu; Wada, Ikuo; Hazama, Akihiro; Nomoto, Yukio; Tada, Yasuhiro; Nakamura, Tatsuo; Omori, Koichi
Abstract: Tracheal epithelial cells maintain airway homeostasis by mediating mucociliary clearance. Following tracheal reconstruction, timely epithelial regeneration is required to prevent respiratory compromise and infectious diseases. To achieve rapid tracheal epithelial regeneration, a heparin cross‐linked collagen sponge containing fibroblast growth factor‐2 (FGF‐2) was prepared as a graft for tracheal reconstruction. The heparin cross‐linked sponge exhibited a high FGF‐2 retaining capacity, and tracheal epithelial and mesenchymal cells cultured in this sponge containing FGF‐2 showed high proliferative capacities. Subsequently, heparin‐free collagen sponge scaffolds (C/F scaffold) and collagen sponge scaffolds cross‐linked with 10 μg/ml heparin retained FGF‐2 (C/H10/F scaffold), and were transplanted into rats with tracheal defects. Invasion of both epithelial and non‐epithelial cells was greater in rats treated with the C/H10/F scaffold at 1 week post‐transplantation than in rats treated with the C/F scaffold. Moreover, at 2 weeks after transplantation, improved cilia formation was observed in the C/H10/F scaffold group, with higher motility and more potent posterior–anterior flow generation than in the C/F scaffold group. These results suggest that heparin improves functional regeneration of tracheal epithelium. Copyright © 2017 John Wiley & Sons, Ltd.